Assessing the Effectiveness of Bisphosphonates for the Prevention of Fragility Fractures: An Updated Systematic Review and Network Meta‐Analyses. (25th March 2022) - Bastounis, Anastasios; Langley, Tessa; Davis, Sarah; Paskins, Zoe; Gittoes, Neil; Leonardi‐Bee, Jo; Sahota, Opinder
ABSTRACT: Bisphosphonates have been found to be effective in preventing fragility fractures. However, their comparative effectiveness in populations at risk has yet to be defined. In light of recent clinical trials, we aimed to compare four bisphosphonates (alendronate, ibandronate, risedronate, and zoledronate) and to identify which are the most effective for the prevention of fragility fractures. This is an update of a systematic review previously published as part of a NICE HTA report. We conducted a systematic review and network meta‐analysis, updating the estimates regarding the comparative effectiveness of the aforementioned bisphosphonates. Studies identified from published and unpublished sources between 2014 and 2021 were added to the studies identified in the previous review. Screening, data extraction and risk of bias assessment were independently undertaken by two reviewers. Outcomes were fractures, femoral neck bone mineral density (BMD), mortality, and adverse events. We identified 25 additional trials, resulting in a total population of 47, 007 participants. All treatments had beneficial effects on fractures versus placebo with zoledronate being the most effective treatment in preventing vertebral fractures (hazard ratio [HR] 0.38; 95% credibility interval [CrI], 0.28–0.49). Zoledronate (HR 0.71; 95% CrI, 0.61–0.81) and risedronate (HR 0.70; 95% CrI, 0.53–0.84) were found to be the most effective treatments in preventing nonvertebral fractures. All treatments were associated with increases in femoral neck BMD versus placebo with zoledronate being the most effective treatment mean difference (MD 4.02; 95% CrI, 3.2–4.84). There was a paucity of data regarding hip and wrist fractures. Depending on its cost‐effectiveness, zoledronate could be considered a first‐line option for people at increased risk of fragility fractures. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.